Modeling Tephra Fall and Sediment-Water Flows to Assess Their Impacts on a Vulnerable Building Stock in the City of Arequipa, Peru - Thouret, J.-C.; Arapa, E.; Charbonnier, S.; Guerrero, A.; Kelfoun, K.; Cordoba, G.; Rodriguez, D.; Santoni, O. (Frontiers in Earth Science, 2022)
Arequipa, Peru’s second economic centre hosting c. 1,110,000 inhabitants, is the largest South American city exposed to a large variety of natural hazards. At least 200,000 live in areas likely to be affected by hazards from El Misti volcano located 17 km to the NE. A multidisciplinary project aims to address impacts of tephra fallout and frequent mass flows on the vulnerable building stock and roofs along two ravines that cross the city, enabling decision makers to undertake retrofitting projects and improve urban risk planning. Two recent eruptions, i.e., the 1440-1470 CE Vulcanian event and c. 2070 yr BP Plinian eruption, were chosen as references for probable scenarios of potential tephra fallout impacts from El Misti on the building roofs. Tephra fallout impacts on the city depends on the eruptive style, column height, and patterns of wind directions and velocities over south Peru as well as roof mechanical resistance. Estimates of potential damage levels and cost range values rely on nine structural types and four classes of vulnerable roofs. Simulation runs of hyperconcentrated flows (HCF) and debris flows (DF), using three depth-averaged flow models (Titan2F, VolcFlow and Flo-2D) along two drainage basins on the SW flank of El Misti and across Arequipa, examined three scenarios from a database of 39 recent events and other historical lahars. Simulations were performed. Results showcase the extent towards the city, inundation depths ≤4.6 m, flow velocities ≤9 m/s and dynamic pressure up to 100 kPa from three different magnitude HCFs and DFs. In both ravines, overbank flows occurred in key urban areas due to channel sinuosity and constrictions near bridges. Potential impacts on habitat stem from ranges of flow dynamic pressure and measurements of construction material. We estimated monetary loss of buildings according to HCF and DF scenarios, with the aim to contribute to retrofitting procedure, implementation of defense work, and relocation policy.